Impedance spectroscopy and giant permittivity study of ZnFe2O4 spinel ferrite as a function of frequency and temperature - Hajlaoui, Mohsen Elain; Gharbi, Sirine; Dhahri, Essebti; Khirouni, Kamel (Journal of alloys and compounds, 2022)
•ZnFe2O4 were prepared by the solid-state reaction.•Large value of the dielectric permittivity.•The dielectric process obeys to three relaxation phenomena.•Our samples have a giant permittivity which can be used in energy storage technology. With good stability in temperature and frequency this material proves to be an interesting candidate to replace the materials traditional dielectrics. Spinel ferrites especially zinc ferrites are of enormous importance in technological applications such as chemical sensors, electrical appliances, microwave industries. Their properties are subject to different studies to investigate the involved mechanisms. The present research work undertakes the study of the conductivity and dielectric permittivity of ZnFe2O4 spinel ferrite as a function of frequency and temperature. Thus, we prepared zinc ferrite spinel by the solid-state reaction route. The structural analysis by X-ray diffraction and scanning electronic microscopy shows that the obtained sample is pure, single-phase composed of prismatic grain of crystallites with a size of 72 nm. The impedance, dielectric permittivity and conductivity of zinc ferrite sample were studied in the frequency range 40 Hz–10 MHz and in the temperature range 300–700 K. Dc conductivity is found thermally activated with an activation energy of 236 meV, indicating an electronic conduction process. The variation of the conductivity with frequency follows power low at low frequency and Drude low at high frequency. Such mechanism change is explained by the increase of free carrier density. Three-relaxation process are identified from impedance spectroscopy analysis. Their associated relaxation times are thermally active and the activation energy of the one associated with grain is close to the one obtained from conductivity, indicating the intra grain conduction dominates transport mechanism. Finally, the compound shows a high dielectric constant in a wide range of frequency, making it suitable for super capacitor application